2011
DOI: 10.1002/ird.548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of controlled drainage efficiency in Lithuania

Abstract: Eight-year (2000Eight-year ( -2007 field studies on the effectiveness of controlled drainage in loam sandy soil were carried out in the lowland of Middle Lithuania. The plot, which has existing subsurface water removal systems operating as conventional drainage, was readjusted for groundwater table management. Two separate systems -4.9 ha free drainage (FD) and 5.4 ha controlled drainage (CD) -were arranged. A water level control structure with riser column and hand-operated rigid flap door was installed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…During precipitation events, the drain flow peaks and groundwater table at the impacted plots were at the same level or even exceeded the peaks at the control plots. Beside reducing the drain flow, controlled drainage also resulted in an approximately one-month delay in drain flow compared with the control plots, a similar result being found by Ramoska et al (2011). Furthermore, the drain flow ceased periodically, which might increase the soil water retention time and improve conditions for denitrification.…”
Section: Impact Of Controlled Drainage On Hydrologysupporting
confidence: 66%
See 1 more Smart Citation
“…During precipitation events, the drain flow peaks and groundwater table at the impacted plots were at the same level or even exceeded the peaks at the control plots. Beside reducing the drain flow, controlled drainage also resulted in an approximately one-month delay in drain flow compared with the control plots, a similar result being found by Ramoska et al (2011). Furthermore, the drain flow ceased periodically, which might increase the soil water retention time and improve conditions for denitrification.…”
Section: Impact Of Controlled Drainage On Hydrologysupporting
confidence: 66%
“…Previous 30 studies have demonstrated that use of controlled drainage on fields with periodical increases of the groundwater table may be a targeted mitigation measure to reduce the loading of NO 3 --N from drain pipes (Wesström and Messing, 2007;Wesström et al, 2001;Lalonde et al, 1996;Drury et al, 2014;Gaynor et al, 2002;Skaggs et al, 2010). Controlled drainage has been tested on a wide range of soil types and under various climate conditions, which is reflected in the large variation -from 21to 96 % (9-30 kg N ha -1 yr -1 ) in the efficiency of reducing NO 3 --N loading compared with conventional drainage (Evans et al, 35 1989;Lalonde et al, 1996;Wesström et al, 2001;Ramoska et al, 2011;Drury et al, 2014;Gilliam et al, 1979;Williams et al, 2015;Fang et al, 2012;Tan et al, 1999;Drury et al, 2009;Sunohara et al, 2014;Gaynor et al, 2002). Most studies demonstrate that the decreased NO 3 --N loading is primarily a consequences of reduced drain flow, and a few studies document it to be a combination of reduced drain flow and enhanced denitrification (Lalonde et al, 1996;Wesström et al, 2001;Gilliam et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Popcorn ( reveals that CD provides greater profit to farmers in northwest Ohio by increasing corn, popcorn, and soybean yield by 3.3%, 3.1%, and 2.1%, respectively The water conservation and quality benefits of CD has been well documented (Drury et al 2009;Ramoska et al 2011;Smith and KeUman 2011;Fang et al 2012). Thus, CD has the potential to provide greater profit to farmers in northwest Ohio while maintaining sound conservation practices.…”
Section: Drainage Management Corn (Mg Ha~^)mentioning
confidence: 86%
“…On-station experiments have also reported the efîect of CD on crop yield (Wesstrom and Messing 2007;Ramoska et al 2011). In these studies, observations were comprised of repeated measurements taken from the same experimental unit (i.e., pseudoreplication), which resulted in the lack of independence (Johnson 2006).…”
Section: Northwest Ohio Is An Intensively Drained Region Within the Mmentioning
confidence: 99%
“…In a system under controlled drainage, which allows the water table to rise no higher than 69 cm above the drains, drainage flow duration is annually reduced from 40 to 62 % (Ramoska et al, 2009). As you can see, depending on the weather conditions, controlled drainage application throughout the growing period reduces drainage water amount by 25 %, and nitrate washing by 20-28 %, and increases the output by 5.6-10 %.…”
Section: Introductionmentioning
confidence: 99%